Integrating International Humanitarian Law and Human Rights in the Use of AI for Conflict Prevention in Outer Space - Yusmita Sari; Farhani Nabiha Binti Mohd Yazi; Rizqiana Arifatul Husna (Indonesian Journal of Law and Islamic Law (IJLIL), 2025)
The rapid increase of space debris and the accelerating use of anti-satellite (ASAT) weapons have generated complex legal challenges that threaten orbital sustainability, global security, and civilian infrastructure. This study examines how International Humanitarian Law (IHL) can be integrated into the governance of artificial intelligence (AI) used in space debris management as a preventive mechanism against the escalation of armed conflict in outer space. Using a normative juridical method supported by textual, comparative, and case-study analyses, this research evaluates key international legal instruments including the Outer Space Treaty (1967) and Additional Protocol I (1977) alongside case studies of the 2007 Chinese and 2021 Russian ASAT tests. The findings demonstrate that the IHL principles of distinction, proportionality, and precaution can be operationalized into AI algorithms to enhance object identification accuracy, minimize civilian harm, and reduce the risk of inadvertent conflict. This study identifies critical governance gaps, particularly in the ambiguous interpretation of “peaceful use,” weak verification mechanisms, and the absence of accountability structures for AI-driven orbital activities. The research contributes a novel framework for embedding IHL into AI design parameters, positioning AI not merely as a technological tool but as a strategic legal instrument for safeguarding orbital stability. Strengthening international space law through transparency norms, AI verification protocols, and updated treaty provisions is therefore essential to ensure outer space remains a peaceful and sustainable global commons for future generations.